2012
DOI: 10.2147/ijn.s32630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polymer molecular weight on relative oral bioavailability of curcumin

Abstract: Background: Polylactic-co-glycolic acid (PLGA) nanoparticles have been used to increase the relative oral bioavailability of hydrophobic compounds and polyphenols in recent years, but the effects of the molecular weight of PLGA on bioavailability are still unknown. This study investigated the influence of polymer molecular weight on the relative oral bioavailability of curcumin, and explored the possible mechanism accounting for the outcome. Methods: Curcumin encapsulated in low (5000-15,000) and high (40,000-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…29 However, PGA-co-PCL has a high degree of hydrophobicity. 30 PGA-co-PCL NPs can be rapidly removed by the reticuloendothelial system when they are intravenously injected into the body. 31,32 These drawbacks can be overcome by introduced D-α-tocopheryl polyethylene glycol (PEG) 2000 succinate (TPGS 2k ) to PGA, PCL, and PGA-co-PCL.…”
Section: Introductionmentioning
confidence: 99%
“…29 However, PGA-co-PCL has a high degree of hydrophobicity. 30 PGA-co-PCL NPs can be rapidly removed by the reticuloendothelial system when they are intravenously injected into the body. 31,32 These drawbacks can be overcome by introduced D-α-tocopheryl polyethylene glycol (PEG) 2000 succinate (TPGS 2k ) to PGA, PCL, and PGA-co-PCL.…”
Section: Introductionmentioning
confidence: 99%
“…4,[9][10][11][12][13] Our hypothesis is supported by previous studies that reported that encapsulated CUR with PLGA-based nanoparticles administrated orally to rats increased CUR levels in the plasma. [14][15][16][17][18] However, to the best of our knowledge, there are no data about CURG, despite the fact that it is the main metabolite of CUR found in the plasma. Therefore, it is not clear whether CUR nanoparticles (CUR-NP) actually improve the intestinal absorption of CUR.…”
mentioning
confidence: 99%
“…35,36 Researchers have also investigated nanoscale formulations of curcumin, such as liposomes, microemulsions, and micelles, for potential therapeutic applications. [37][38][39][40][41][42] The nanoscale effect by which such drug delivery systems improve the oral performance of curcumin involves increasing the surface area and interactions of curcumin, thereby providing better water dispersibility to enhance its absorption. 38 In this study, a novel silica-coating liposomal strategy was used to construct a nanohybrid formulation for curcumin.…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39][40][41][42] The nanoscale effect by which such drug delivery systems improve the oral performance of curcumin involves increasing the surface area and interactions of curcumin, thereby providing better water dispersibility to enhance its absorption. 38 In this study, a novel silica-coating liposomal strategy was used to construct a nanohybrid formulation for curcumin. Silica-coated FLs were prepared by the dry-film dispersion method, combined with a sol-gel precipitation upon the liposomal surface.…”
Section: Resultsmentioning
confidence: 99%